Legal Review of Women’s Representation in Elections 2024 (Case Study in Muna Regency, Southeast Sulawesi) - Goro, Sitti Nurhaliza; Bariun, L.M; Muhram, La Ode (International Journal of Management and Education in Human Development, 2025)
Research purposes done namely: 1. For know and understand representation Woman in elections 2024 in Muna Regency 2. To find out what is hindering candidate legislative Woman in fulfil its representation . Research This held in Muna Regency , precisely at the Commission Office General Election (KPU) and Party Offices Politics , with use type study that is normative empirical . The data collection method used is studies documents , surveys field and interviews with use analysis descriptive qualitative . Based on results study can known: 1) Representation Woman in Election In 2024 in Muna Regency, the total number of candidates contesting legislature as many as 387 consisting of of 243 (62.79%) men and 144 (37.21%) women. Of the 15 parties contesting in the 2019 Election , the quantity legislative candidate Woman recorded as many as 166 (39.71%) and decreasing to 144 (37.21%) in the 2024 Election . This means that there will be decline representation women in the DCT by 3.65% in the 2024 Election . 2). 2. Obstacles candidate legislative Woman in fulfil its representation There are 3, namely : Double Burden Resistance , Double Burden Resistance Financial and Obstacles Quota without Cadres.